ANALISIS PENGARUH KOMPETENSI TEKNIS DAN LINGKUNGAN KERJA TERHADAP KINERJA BIDAN DENGAN MEDIASI MOTIVASI (STUDI DI PUSKESMAS EKS KAWEDANAN PATI ) (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aimed to determine the effect of technical competence, work environment and motivation on employee performance midwife at the health center Starch. It is based on the phenomenon that is the Infant Mortality Rate (IMR) and Maternal Mortality Rate (MMR) in Indonesia is still quite high compared to other ASEAN countries. Based on the results of supervision by the District Health Officer Subag Pati on the performance of midwives, it is known that 20% of midwives are not domiciled in the local region. Maternal and child health visits in the Work Area Health Service Pati still lacking the K1 visits reached 5.52% of the targets to be achieved by 8.33%, the new K2 reached 5.81% of the targets to be achieved is 7.91% , K3 only reached 6.39% of the targets to be achieved by the new K4 7.91% and reached 6.97% of the target should be at 7.91%. This research was conducted on former midwife at the health center sub district of Pati as many as 109 people, using census techniques. Statistical techniques are used to test the validity of the components of matrix, Cronbach alpha reliability test, multiple regression analysis, t test and adjusted r2 with r square. Results reveal that the effect on the motivation of technical competence of midwives in health centers Kawedanan ex Starch (sig = 0.000). Work environment has a positive effect on the motivation of midwives in health centers Kawedanan ex Starch (sig = 0.000). Technical competence has a positive effect on employee performance at the District Health Office Pati (sig = 0.000). Work environment affect the job performance of midwives Motivation does not mediate the effect on the performance of the technical competence of midwives in health centers Kawedanan former Starch. Motivation does not mediate environmental influences on the performance of midwives working in health centers Kawedanan former Starch. Keywords: technical competence, work environment, motivation and performance